O020/#1031 Fragmentation of care and survival in high-grade endometrial cancer: a population-based cohort study. (4th December 2022) - Nica, Andra; Sutradhar, Rinku; Kupets, Rachel; Covens, Allan; Vicus, Danielle; Li, Qing; Ferguson, Sarah; Gien, Lilian
Abstract : Objectives: Fragmentation of cancer care (FC) occurs when patients receive treatment across several different hospitals. Patients with high-grade endometrial cancer often require adjuvant treatment after surgery, and it is unknown if change of location during treatment impacts patient outcomes. Methods: This population-based retrospective cohort study included patients diagnosed between 2003–2017 with high-grade endometrial cancer who received adjuvant treatment post-operatively. Non-fragmented care (NFC) was defined as receiving surgery and adjuvant treatment at the same institution. The primary outcome was overall survival (OS). Results: We identified 1, 795 patients, of whom 583 (32.5%) had FC. Patients with NFC were more likely to have had surgery by a Gynecologic Oncologist (92.4 vs 58.8%, p<0.001), surgical staging (66.6 vs 44.8%, p<0.001), and less travel for surgery (mean 30.8 km vs 93.7 km, p<0.001). They were less likely to receive chemotherapy (26.3 vs 30%, p<0.001) and chemoradiation (38.4 vs 41.3%, p<0.001). Median survival was 9 years. There was no significant difference in OS between patients who received FC and NFC. 92.4 and 93.5% of the patients in the FC and NFC groups were treated at a specialized gynecologic oncology centre for at least part of their treatment (surgery, adjuvant treatment or both). Conclusions: We have previously shown that regionalization of surgery in high-grade endometrial cancer is associated with improved survival. Fragmentation of surgery and adjuvant treatment in this population does not have an adverse effect on survival. After receiving surgical treatment with a Gynecologic Oncologist, these patients may receive adjuvant treatment closer to home to decrease financial and travel burden.